Health Resort Treatment for COVID-19 Patients: a Review - Maria S. Petrova; Maya A. Khan (Ministry of Health of the Russian Federation. National Medical Research Center of Rehabilitation and Balneology, 2023)
INTRODUCTION. To date, one of the important tasks of Russian healthcare is the development and improvement of sanatoriumtreatment. The article highlights topical issues of development and improvement of sanatorium treatment of children in institutionssubordinate to the Administrative Department of the President of the Russian Federation. It presents the data on the peculiaritiesof the functioning of the II and III stages of medical rehabilitation in the conditions of health resort institutions on the basis of therehabilitation department of the children's sanatorium "Polyany", where a wide range of innovative technologies of physiotherapy andkinesiotherapy are successfully applied. The high availability of sanatorium-resort treatment for children registered at a dispensaryin a Children's medical center is shown. Data are published on the effective use of the bed capacity of health resort institutionssubordinate to the Administrative Department of the Russian Federation, primarily for the treatment and medical rehabilitation ofchildren with chronic diseases. The article describes the organization and modern technologies of medical rehabilitation of childrenwith diseases of musculoskeletal system, respiratory organs, digestion, genitourinary system, in institutions subordinated to theAdministrative Department of the President of the Russian Federation. There are data on the organization of medical rehabilitationof children who have had COVID-19. A 3-stage system of restorative treatment, indications and non-drug technologies of medicalrehabilitation of such patients are shown.AIM. To assess the current state of the health resort care for children in institutions subordinate to the Administrative Department ofthe President of the Russian Federation.CONCLUSION. In order to further improve the sanatorium treatment of children in institutions subordinate to the AdministrativeDepartment of the President of the Russian Federation, there are of the necessity: a personalized approach to the development ofsanatorium-treatment programs for children, an optimization of the II and III sanatorium stages of medical rehabilitation of children, anintroduction of innovative technologies of medical rehabilitation of children in the practical activities of sanatoriums, an integration ofresearch results into the practice of s‑anatorium treatment of children and continuous professional development of specialists, workingin health resorts.